Making Cyberspace Safe for Democracy: The New Landscape of Information Competition. - Rosenberger, Laura (Foreign Affairs)
The article focuses on the need of making cyberspace safe for democracy. It mentions surveillance, censorship, and the manipulation of information, authoritarian regimes shore up their power at home while weakening democratic competitors abroad. It also mentions Russia's hacking operations and use of social media to manipulate public discourse in the U.S. caught U.S. policymakers off-guard and Russian interference in presidential elections of the U.S.